2017
DOI: 10.5858/arpa.2017-0164-oa
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Confocal Fluorescence Microscopy for Rapid Evaluation of Tissues in Surgical Pathology Practice

Abstract: - The ease and speed of acquisition of CFM images together with the resolution and resemblance of the CFM images to hematoxylin-eosin sections suggest that the CFM platform has excellent potential for use in surgical pathology practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…In the 1980's, Tejada et al developed a specialized test with sperm AO fluorescence staining to determine male fertility (31). Krishnamurthy et al showed that staining of breast, lung, kidney, and liver tissues with AO alone and subsequent imaging with confocal laser microscopy practically does not differ in efficiency from staining with H&E (32). Moreover, AO staining was much faster and easier than H&E (32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1980's, Tejada et al developed a specialized test with sperm AO fluorescence staining to determine male fertility (31). Krishnamurthy et al showed that staining of breast, lung, kidney, and liver tissues with AO alone and subsequent imaging with confocal laser microscopy practically does not differ in efficiency from staining with H&E (32). Moreover, AO staining was much faster and easier than H&E (32).…”
Section: Resultsmentioning
confidence: 99%
“…Krishnamurthy et al showed that staining of breast, lung, kidney, and liver tissues with AO alone and subsequent imaging with confocal laser microscopy practically does not differ in efficiency from staining with H&E (32). Moreover, AO staining was much faster and easier than H&E (32). In yet another application, Wang et al used AO for rapid non-destructive imaging of whole prostate biopsies using video-rate fluorescence structured illumination microscopy and demonstrated its feasibility as an alternative to destructive pathology (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive list of potential EVM applications was developed from a review of the published literature performed as part of the annual update of the CAP IVM Resource Guide, as well as from expert opinion within the group. 7,[9][10][11][12][13] Three EVM applications were then selected for development of detailed FRs based on currently published studies and likely wide use in pathology practice. The FR categories were formulated to encompass the requirements for pathology practice and compliance with applicable guidelines and regulations.…”
Section: Designmentioning
confidence: 99%
“…The consensus opinion was that EVM systems should have resolution comparable to a magnification of 310 to 320 (0.5-1.0 lm resolution) in a standard light microscope. 7 This should be sufficient to assess tissue adequacy for diagnosis or to identify lesional tissue for special studies or biorepository, including assessing cellularity and viability. For margin assessment, healthy or benign tissue should be able to be distinguished from malignant (invasive or in situ cancer).…”
Section: Evm Functional Requirementsmentioning
confidence: 99%